Dung beetles (Coleoptera: Scarabaeidae) in grazing lands of the Neotropics: A review of patterns and research trends of taxonomic and functional diversity, and functions - Arellano, Lucrecia; Noriega, Jorge Ari; Ortega-Martínez, Ilse J.; Rivera, José D.; Correa, César M. A.; Gómez-Cifuentes, Andrés; Ramírez-Hernández, Alfredo; Barragán, Felipe (Frontiers in Ecology and Evolution, 2023)
Dung beetles are one of the most representative groups of insects associated with livestock, as they take advantage of the manure of livestock for food and reproduction. They have been widely used as a bio-indicator group to evaluate their responses to land-use change and other environmental disturbances by analyzing species diversity at different spatial and temporal scales. However, the impacts of livestock management practices, forms, and history on dung beetle diversity are still poorly understood. This paper is an exhaustive and systematic review of the existing peer-reviewed and indexed literature on the taxonomic diversity (species richness and composition), functional diversity, and ecological functions of dung beetles from different provinces and biogeographic domains in tropical grazing lands of the Neotropics. We analyzed the timeline of the studies conducted so far, and we detected increasing literature produced mainly in South America. We included the most frequent objectives, tendencies, software, and statistical analyses. Given the significant heterogeneity of livestock landscapes in the Neotropics, the reviewed studies have conceptualized broadly what a pasture is, and the authors have used different descriptions of other grazing lands. Additionally, management data and livestock practices vary widely among studies, and management history is poorly described. In future research, it is relevant to include as much information as possible and the consequences of different livestock management practices on additional ecological attributes of dung beetle assemblages at different landscape scales (spatial and temporal) to predict how ecological processes change in Neotropical landscapes. Considering the importance of the data to be included in future work, we propose a collection format to unify the information collected in the field when conducting ecological studies in grazing lands. Moreover, we define a classification system to homogenize the features that distinguish the multiple tropical grazing lands reported in the literature. Preserving dung beetle diversity and associated ecological functions is urgent for maintaining ecosystem services in grazing lands. The challenge for research institutions is to continue filling gaps in knowledge to help those who work in transferring knowledge, to help ranchers exercise better options for more sustainable livestock farming, and to publish results for conservation decision-making.